IMPLEMENTATION OF NATIONAL CURRENCIES IN FOREIGN TRADE SETTLEMENTS: PREREQUISITES, LIMITATIONS, PERSPECTIVES - I. A. Balyuk (Финансы: теория и практика)
A tendency to implement national currencies in foreign trade settlements on a wider scale reflects a multipolar essence of the modern world. It is quite logical and natural result of increasing risks lately connected with the key world currencies. Different countries are interested in reducing dependence on the international currency and financial markets when global geopolitical situation is getting worse.The article examines prerequisites and preconditions for expanding the scope of implementation of national currencies in foreign trade settlements between different countries. The analysis of practical experience of implementation of national currencies in foreign trade settlements has allowed to highlight the «bottlenecks» and problems hindering more active implementation of national currencies by the national participants of foreign economic relations. Current trends and perspectives of implementation of national currencies in foreign trade settlements are discussed in general terms by taking into consideration Russian rouble and Renminbi.The analysis substantiates the need to eliminate existing law, administrative, financial and economic barriers hampering the national participants of foreign economic relations to efficiently conduct business activities in the domestic financial markets, and to ensure favourable market conditions by the national financial institutions.